2002
DOI: 10.1186/1471-230x-2-12
|View full text |Cite
|
Sign up to set email alerts
|

13C-Urea breath test threshold calculation and evaluation for the detection of Helicobacter pylori infection in children

Abstract: Background: The 13 C-urea breath test (UBT) is performed in adults and children with epigastric pain for non-invasively diagnosing a suspected H. pylori infection. Criteria for UBT interpretation have not been generally agreed on and test reliability has not been established in children of different ages. This study aimed at identifying reliable UBT thresholds in children by using 251 UBTs in conjunction with reference histology and by analyzing 1232 UBTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…The cut-o value obtained by using the maximum of sensitivity plus speciÿcity as criteria are smaller than the cut-o values using the maximum of positive predictive plus negative predictive values and the minimum probability of misclassiÿcation as the criteria. This agrees with the results from a recent study of German children [20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The cut-o value obtained by using the maximum of sensitivity plus speciÿcity as criteria are smaller than the cut-o values using the maximum of positive predictive plus negative predictive values and the minimum probability of misclassiÿcation as the criteria. This agrees with the results from a recent study of German children [20].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, a recent study of 3 months-5 years of age found a cut-o point of 9:1D used a similar analytic method though with a rather large error [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both histology (37) and [ 13 C]-UBT (38)(39)(40) have served as excellent methods for diagnosing H. pylori infection in children, although for the age group younger than 6 years the specificity of [ 13 C]-UBT can be lower (41). In our study, none of the patients was younger than 7 years of age.…”
Section: Discussionmentioning
confidence: 55%
“…Although the 13 C-labeled UBT has been used in children and appears promising, reliability and determination of threshold values have not been adequately validated in multiple, large multicenter, randomized, controlled trials. 23 Serology with immunoglobulin G (IgG) is widely used and is considered the first line of noninvasive diagnostic tests in adults, particularly in Europe, with suspected H pylori infection. Unfortunately, serology does not provide any data as to whether there is active or past infection.…”
Section: Diagnosing H Pylori In Childrenmentioning
confidence: 99%